APPLICATION OF REVERSE FLOTATION METHOD FOR THE UPGRADING OF IRON OXIDE CONTAINED IN CALCINE LATERITE ORE - PRAMUSANTO PRAMUSANTO; NURYADI SALEH; MUTA’ALIM MUTA’ALIM; YUHELDA DAHLAN; Muchtar Aziz (Indonesian Mining Journal, 2008)
Reverse flotation was adopted for Indonesian iron-rich laterite ore from Pomalaa to float siliceous minerals in the separation of iron mineral. Nickel siliceous mineral such as garnierite is one of the silicate minerals containing in laterite ore that are undesirable and must be eliminated from the ore before used as raw material for iron making industry. Calcine laterite product was obtained from reduction process in rotary kiln for 3 hours at 900 °C by transforming limonite/goethite to magnetite containing Fe 45.6 % and Ni 1.16 %. The reverse flotation tests were focused on the separation of iron mineral from nickel mineral using amine complex, ARMAC-C, a commercially available amine thioacetate as collector. Influences of pulp pH, dosages of collector amine complex and frother, and also solid percent of pulp on the reverse flotation of calcine laterite ore were investigated. The optimal condition was obtained at pH 10, collector 1000 g/t and frother 25 g/t at solid percent of 30%. The test results show that after one-stage rough reverse flotation the concentrate had Fe and Ni grades of 77.5% and 0.5% with recoveries of 57.3% and 33.7%, respectively. Therefore, it is possible to use iron-rich lateritic ore to produce magnetic concentrates by using magnetizing roasting followed by reverse iron flotation.